The impact of social financing structures on different industry sectors: A new perspective based on time-varying and high-dimensional methods - Xianghua Wu; Hongming Li; Yuanying Jiang (AIMS Mathematics, 2024)
With the continuous innovation of financial instruments, the financing structure presents a diversified development trend, and the proportion of direct financing in Aggregate Financing to the Real Economy (AFRE) has been increasing. We utilized monthly data from January 2002 to March 2023 to establish a time-varying spillover index model and a large TVP-VAR model in order to investigate the dynamic impact of the social financing structure on various industry sectors. The empirical results suggested that the impact of financing structure on different industry sectors varies. Direct financing had the least impact on the industry compared to on-balance-sheet financing and off-balance-sheet financing. Lagging effects had the most significant influence on all industries. Furthermore, since 2015, the impact of different industries on the proportion of direct financing has significantly changed, indicating that the impact of direct financing on different industries became apparent during the 'stock crash'. Moreover, the impact of different financing methods on the economic development of various industry sectors was susceptible to external events, and the degree of impact varied. Our results are useful in helping policy makers better understand the changes in different industries affected by the financing structure, which can inform their policy formulation.